THE JURIDICAL REVIEW OF WITHDRAWAL ASEAN (ASSOCIATION OF SOUTHEAST ASIAN NATIONS) MEMBER STATES FROM THE ASEAN CHARTER BASED ON THE VIENNA CONVENTION 1969 - Galih Putri Sudarsono (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2014)
State as the main subject of international law has the sovereignty to determine to stay or withdraw from membership of an international organization. ASEAN as an international organization has a constituent instrument. ASEAN member states are bound to comply the obligations specified in the ASEAN Charter. However, the ASEAN Charter as the constituent instrument does not set the withdrawal clause. Thus, the possibility of withdrawal of ASEAN members become blurred and indistinct.Keyword : ASEAN Charter, Withdrawal, Vienna Convention 1969